Inclusive Education Technologies: Emerging Opportunities for People with Visual Impairments - , Oussama Metatla, Marcos Serrano, Christophe Jouffrais; Thieme, Anja; Kane, Shaun; Branham, Stacy; Brule, Emeline; Bennett, Cynthia L. (CHI 2018 Extended Abstracts, 2018)
Technology has become central to many activities of learning, ranging from its use in classroom education to work training, mastering a new hobby, or acquiring new skills of living. While digitally-enhanced learning tools can provide valuable access to information and personalised support, people with speciﬁc accessibility needs, such as low or no vision, can often be excluded from their use. This requires technology developers to build more inclusive designs and to offer learning experiences that can be shared by people with mixed-visual abilities. There is also scope to integrate DIY approaches and provide specialised teachers with the ability to design their own low cost educational tools, adapted to pedagogical objectives and to the variety of visual and cognitive abilities of their students. For researchers, this invites new challenges of how to best support technology adoption and its evaluation in often complex educational settings. This workshop seeks to bring together researchers and practitioners interested in accessibility and education to share best practices and lessons learnt for technology in this space; and to jointly discuss and develop future directions for the next generation design of inclusive and effective education technologies.